Des talus pleins les yeux - Denis Delbaere; Sabine Ehrmann (Projets de Paysage)
Because of its scale, the representation of the landscape always poses daunting problems. These problems are greater in the case of urban fringes due to their indeterminate nature, the dilution of their limits and the vagueness of their territorial status in the spatial perception of societies. By studying the case of the embankments, shoulders and abandoned infrastructures of the Likoto Eurometropolis (Lille/Kortijk/Tournai), this research on “marginal spaces” was confronted with an extreme feature of the urban fringe, the tenuousness and infinite linearity of which render it all the more elusive. As a result, embankments, ever present in the view most of us have of the places we travel through every day when using motorways or railways, are also the ones we take the least notice of since we perceive them simply as green spaces devoid of any intrinsic value. How can spaces which are destined to remain invisible be represented ? This article describes and records the problems which confront two modes of representation adopted by researchers – photography and cartography. It shows the ways these techniques, separately, together, and finally in the service of one another, have been used to attempt to show the invisible effectively, with the risk of adopting an approach which might seek to invent, through the process of visualisation, the object of its investigation. Can the prospective status acquired by the visualisation of space be considered as one of the intrinsic aspects of an approach to envisioning the landscape ?